2016
DOI: 10.1016/j.bbadis.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Regulated Inhibitor of Apoptosis 1 (TRIAP1) stable silencing increases late apoptosis by upregulation of caspase 9 and APAF1 in RPMI8226 multiple myeloma cell line

Abstract: In the present study, we demonstrated effects of TRIAP1 silencing on RPMI8226 MM cell line and established its mechanism mediated through APAF1 and Caspase 9. No relevant effect was found after gene silencing in U266 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…A previous study indicated that TRIAP1 inhibition could induce cell apoptosis by upregulating caspase-9 and apoptotic protease-activating factor 1 (APAF1) (17). Therefore, whether caspase-9 and APAF1 were involved in regulating PLC/PRF/5 cell apoptosis by miR-125a-5p was investigated using western blots.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that TRIAP1 inhibition could induce cell apoptosis by upregulating caspase-9 and apoptotic protease-activating factor 1 (APAF1) (17). Therefore, whether caspase-9 and APAF1 were involved in regulating PLC/PRF/5 cell apoptosis by miR-125a-5p was investigated using western blots.…”
Section: Resultsmentioning
confidence: 99%
“…Some genes including TRIAP1 are reported to be up-regulated and play a crucial role in multiple myeloma [25,26]. A genome-wide genetic screen in human cells indicates that TRIAP1 is a specific repressor of p21, one p53 target gene [27].…”
Section: Mir-107 Negatively Correlates With Triap1 In Clinical Lung Cmentioning
confidence: 99%
“…One of these genes, P53CSV/TRIAP1 (TP53 regulated inhibitor of apoptosis 1), was overexpressed in more than 90% of MM cases. TRIAP1 activates apoptotic pathways through interaction with HSP70, preventing APAF-1 (apoptosis protease activating factor 1), cytochrome c , and caspase-9 apoptosome complex formation [ 8 , 9 ]. Overexpression of HSP70 may provide a selective advantage for tumor cell survival due in part to its ability to inhibit cell death through APAF-1 and caspase 9 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%